JWST Measurements of Neutral Hydrogen Fractions and Ionized Bubble Sizes at z = 7–12 Obtained with Lyα Damping Wing Absorptions in 27 Bright Continuum Galaxies - Hiroya Umeda; Masami Ouchi; Kimihiko Nakajima; Yuichi Harikane; Yoshiaki Ono; Yi Xu; Yuki Isobe; Yechi Zhang (The Astrophysical Journal, 2024)
We present volume-averaged neutral hydrogen fractions x _H I and ionized bubble radii R _b measured with Ly α damping wing absorption of galaxies at the epoch of reionization. We combine JWST/NIRSpec spectra taken by the CEERS, GO-1433, DDT-2750, and JADES programs and obtain a sample containing 27 bright UV-continuum ( M _UV < −18.5 mag) galaxies at 7 < z < 12. We construct four composite spectra binned by redshift and find the clear evolution of the softening break toward high redshift at rest-frame 1216 Å, suggesting an increase of Ly α damping wing absorption. We estimate Ly α damping wing absorption in the galaxy spectra with realistic templates including Ly α emission and circumgalactic medium absorptions. Assuming the standard inside-out reionization picture having an ionized bubble with radius R _b around a galaxy embedded in the intergalactic medium with x _H I , we obtain x _H I ( R _b ) values generally increasing (decreasing) from ${x}_{{\rm{H}}\,{\rm\small{I}}}={0.53}_{-0.47}^{+0.18}$ to ${0.92}_{-0.10}^{+0.08}$ ( $logR_{b}={1.67}_{-0.16}^{+0.14}$ to $-{0.69}_{-0.24}^{+0.89}$ comoving Mpc) at redshift ${7.12}_{-0.08}^{+0.06}$ to ${9.91}_{-1.15}^{+1.49}$ . The redshift evolution of x _H I indicates a moderately late reionization history consistent with the one previously suggested from the electron scattering of cosmic microwave background and the evolution of UV luminosity function with an escape fraction f _esc ∼ 0.2. Our R _b measurements suggest that bubble sizes could be up to a few dex larger than the cosmic average values estimated by analytic calculations for a given x _H I , while our R _b measurements are roughly comparable with the values for merged ionized bubbles around bright galaxies predicted by recent numerical simulations.